Automated monitoring of the crack propagation in mode I testing of thermoplastic composites by means of digital image correlation. (February 2020) - Khudiakova, A.; Grasser, V.; Blumenthal, C.; Wolfahrt, M.; Pinter, G.
Abstract: One of the main challenges of the mode I double cantilever beam (DCB) test is the simultaneous determination of the applied load and displacement with the developing delamination length. The present work addresses this issue by side-view tracking the crack propagation by means of digital image correlation (DIC). Two different reduction methods were developed to determine the crack length from the DIC data. On the one hand, the crack tip position was defined by the high strain concentration in the immediate vicinity of the crack tip, and on the other hand, by crack tip opening displacement (CTOD). The data obtained enabled the calculation of the energy release rate of carbon fibre reinforced thermoplastic specimens with either run-arrest or stable crack extension. For reasons of comparability, top surface analysis (TSA), as recently reported, was also carried out. Following this approach, the crack propagation was tracked applying DIC to the top specimen surface. The methods developed showed a good correlation with both the standardised procedure and TSA. It was shown that DIC can be used as an alternative to the conventional optical measuring tools to follow the crack propagation in the mode I DCB test. Highlights: DIC was applied to follow delamination in the mode I DCB test. The crack tip was localised by two methods newly developed. The crack length was defined by the strain and crack tip opening displacement criteria. The results were in agreement with both the standardised procedure and the top surface analysis. DIC is a promising technique to follow the crack propagation in the mode I DCB test.